Enhanced Photocatalytic Degradation of Rhodamine B Using C/Fe Co-Doped Titanium Dioxide Coated on Activated Carbon - Thuy Le Thi Thanh; Lan Nguyen Thi; Trinh Tran Dinh; Noi Nguyen Van (Journal of Chemistry, 2019)
Carbon and iron co-doped titanium dioxide catalyst coated on activated carbon (Fe-C-TiO2/AC) was successfully synthesized using the sol-gel method, followed by hydrothermal treatment. Commercial activated carbon was treated by HNO3 prior to being coated by the as-synthesized catalyst. The composite was characterized by XPS, XRD, UV-Vis spectrophotometry, IR, TEM, HR-TEM, and BET. The performance of the supported catalysts was evaluated in the degradation of rhodamine B (RhB) in the solution under visible-light irradiation. The results showed that, with the appropriate amount of activated carbon, prepared Fe-C-TiO2/AC catalysts exhibited higher catalytic activities and Fe-C-TiO2/AC system showed the best performance. The photocatalytic degradation efficiency of Fe-C-TiO2/AC was enhanced due to the synergistic effect between AC (adsorption effect) and Fe-C-TiO2 (photocatalysis effect). This facilitated the photocatalytic degradation of RhB by Fe-C-TiO2.